WHAT IS THE YOUNG GENERATION INTENSION IN DOING TAX EDUCATION? - Mirza Maulinarhadi Ranatarisza; Virda Nur Hidayah; Ria Ika Novitasari (Erudio Journal of Educational Innovation, 2019)
The behavior of the young generation to be willing to carry out tax education through the tax volunteer program is classified as a useful activity in increasing tax compliance. The theory of planned behavior is one pattern that can be used to identify factors that influence a behavior, in this case is the behavior of conducting tax education through a tax volunteer program. The purpose of this study is to find empirical evidence about the influence of attitudinal factors, subjective norms, perceptions of controlling behavior and intention of the younger generation in this case students towards the behavior of conducting tax education through a tax volunteer program.               This type of research is descriptive research verification with a quantitative approach. This research was conducted on tax volunteers registered through the tax center of the UB Faculty of Administrative Sciences, as many as 80 people from. Sampling is done using Saturated sampling techniques, ie all populations are taken as a whole sample. Variables in the study included independent variables consisting of attitude (X1), social norms (Subjective Norm) (X2), and perceptions of behavioral control (X3) (X3). The intervening variable used is intense (Y). the dependent variable used is student behavior in conducting tax education through a tax volunteer (Z) program. The test used in testing the research instrument is validity and reliability testing. The stages of analysis used in this study are verification analysis including; Test path analysis (path analysis), coefficient of determination analysis, hypothesis testing using Statistical Package for Social Science (SPSS) software.               The results of this research are, known that Attitude (X1), and the perception of the ability to control (Perceived Behavioral Control) (X3) affect the behavior of young generation as a students in conducting tax education with a tax volunteer program (Z) through intention (Y) as an intermediate variable. Or in other words attitudes and perspectives controlling the behavior of a student affect their intentions / intentions in carrying out a behavior, which in this case is doing tax education with a tax volunteer program.